State Ownership : A Residual Role? - Perotti, Enrico 1991- (The World Bank, 2004)
Perotti reviews the state of thinking on the governance role of state ownership. He argues that a gradual transfer of operational control and financial claims over state assets remains the most desirable goal, but it needs to be paced to avoid regulatory capture, and the capture of the privatization process itself. In addition, the speed of transfer should be timed on the progress in developing a strong regulatory governance system, to which certain residual rights of intervention must be vested. In many countries institutional weakness limits regulatory capacity and reliability, yet the author's conclusion is that in such environments, maintaining state control undermines the very emergence of institutional capacity, and so the balance should tip toward progressively less direct state control. After all, what are "institutions" if not governance mechanisms with some degree of autonomy from both political and private interests? The gradual creation of institutions partially autonomous from political power must become central to the development of an optimal mode of regulatory governance. The author offers some suggestions about creating maximum accountability in regulatory governance, in particular creating an internal control system based on a rotating board representative of users, producers, and civic organizations, to be elected by a process involving frequent reporting and disclosure. This paper—a product of the Global Corporate Governance Forum, Investment Climate Unit—is part of a larger effort in the department to improve the understanding of corporate governance reform in developing countries